The Cyclic AMP Phenotype of Fragile X and Autism - Kelley, Daniel J (2008)
Cyclic AMP (cAMP) is a second messenger involved in many processes including mnemonic processing and anxiety. Memory deficits and anxiety are noted in the phenotype of fragile X (FX), the most common heritable cause of mental retardation and autism. Here we review reported observations of altered cAMP cascade function in FX and autism. Cyclic AMP is a potentially useful biochemical marker to distinguish autism comorbid with FX from autism per se and the cAMP cascade may be a viable therapeutic target for both FX and autism.